Konsep Pendidikan Anak Menurut Ibnu Khaldun (Studi Atas Kitab Muqaddimah) - Falah, Ahmad (THUFULA, 2014)
The concept of a child’s education, according to Ibn Khaldunin his book Prolegomena can be grouped into several important part ofthe concept and his thinking, ie on the basics of education, the divisionof sciences, there is science and science naqliyah aqliyah, the basicprinciples of Islamic education, educational purposes, methods, materials,nature educators and students as well as a discussion of the teachingof the Koran and Arabic for the countries of the Arab world and AfricaThe purpose of education according to Ibn Khaldun is the religious and moraleducation, Islamic education and the world’s attention to the interests ofreligion, Islamic education prioritize aspects of expediency, Islamic educationto educate children to study not merely for science alone but for the provisionsthat can be applied to the next life, Islamic education is concerned withvocational education (vocational), art, carpentry in order to find work andgood luck.Curriculum (material) according to Ibn Khaldun is material to the base rateincludes: Koran, joints religion, reading, writing, arithmetic, the basics of theArabic language, moral education, stories, syi’ir and ktrampilan, and materialto a high level (higher education) include religion and literatures, and sciencesthat support the life eg foreign language.